Association of Body Mass Index with Juvenile Idiopathic Arthritis Disease Activity: a Portuguese and Brazilian Collaborative Analysis - Neto, A (2021)
Objective: To investigate the relationship between body mass index (BMI) and disease activity in patients with Juvenile Idiopathic Arthritis (JIA). Methods: Patients with JIA, aged ≤18 years, registered at the Rheumatic Diseases Portuguese Register (Reuma.pt) in Portugal and Brazil were included. Ageand sex-specific BMI percentiles were calculated based on WHO growth standard charts and categorized into underweight (P<3), normal weight (3≤P≤85), overweight (85<P≤97) and obesity (P>97). Disease activity was assessed by Juvenile Arthritis Disease Activity Score (JADAS-27). Uni- and multivariable analyses were performed. Results: A total of 275 patients were included. The prevalence of underweight, normal weight, overweight and obesity was 6.9%, 67.3%, 15.3% and 10.5%, respectively. Underweight patients had significantly higher number of active joints (p<0.001), patient’s/parent’s global assessment of disease activity (PGA) (p=0.020), physician’s global assessment of disease activity (PhGA) (p<0.001), erythrocyte sedimentation rate (ESR) (p=0.032) and overall higher JADAS-27 (p<0.001), compared to patients with normal weight, overweight and obesity. In the multivariable regression, normal weight (B=-9.43, p<0.01), overweight (B=-9.30, p=0.01) and obesity (B=-9.12, p=0.01) were significantly associated with lower disease activity compared to underweight, when adjusted for age, gender, country, ethnicity, JIA category and therapies used. The diagnosis of RF- (B=3.65, p=0.006) or RF+ polyarticular JIA (B=5.29, p=0.024), the absence of DMARD therapy (B=5.54, p<0.001) and the use of oral GC (B=4.98, p=0.002) were also associated with higher JADAS-27. Conclusion: We found an independent association between underweight and higher disease activity in patients with JIA. Further studies are needed to understand the underlying mechanisms of this association.